Question
upstudy study bank question image url

If \( \cos ^{2} 23^{\circ}=t \), determine the following in terms of \( t \) : (1) \( \sin ^{2} 337^{\circ} \) (2) \( \sin 23^{\circ} \) (3) \( \cos 46^{\circ} \) (4) \( \sin 46^{\circ} \) (5) \( \tan \left(-226^{\circ}\right) \) (6) \( \sin 37^{\circ} \)

Ask by Rogers Schofield. in South Africa
Feb 18,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

1. \( \sin^2 337^\circ = 1 - t \) 2. \( \sin 23^\circ = \sqrt{1 - t} \) 3. \( \cos 46^\circ = 2t - 1 \) 4. \( \sin 46^\circ = 2\sqrt{t(1 - t)} \) 5. \( \tan(-226^\circ) = -\frac{2\sqrt{t(1 - t)}}{2t - 1} \) 6. \( \sin 37^\circ = \frac{\sqrt{3}}{2}\sqrt{1 - t} + \frac{1}{2}\sqrt{t} \)

Solution

To solve the problem, we will use the known relationships between trigonometric functions and the given value \( t = \cos^2 23^\circ \). ### Step 1: Determine \( \sin^2 337^\circ \) Using the identity \( \sin(360^\circ - x) = -\sin(x) \): \[ \sin 337^\circ = \sin(360^\circ - 23^\circ) = -\sin 23^\circ \] Thus, \[ \sin^2 337^\circ = (-\sin 23^\circ)^2 = \sin^2 23^\circ \] Using the Pythagorean identity \( \sin^2 x + \cos^2 x = 1 \): \[ \sin^2 23^\circ = 1 - \cos^2 23^\circ = 1 - t \] ### Step 2: Determine \( \sin 23^\circ \) Using the identity \( \sin^2 x + \cos^2 x = 1 \): \[ \sin 23^\circ = \sqrt{1 - \cos^2 23^\circ} = \sqrt{1 - t} \] ### Step 3: Determine \( \cos 46^\circ \) Using the double angle formula \( \cos(2x) = 2\cos^2(x) - 1 \): \[ \cos 46^\circ = \cos(2 \times 23^\circ) = 2\cos^2 23^\circ - 1 = 2t - 1 \] ### Step 4: Determine \( \sin 46^\circ \) Using the identity \( \sin(90^\circ - x) = \cos x \): \[ \sin 46^\circ = \cos(90^\circ - 46^\circ) = \cos 44^\circ \] Using the identity \( \cos(90^\circ - x) = \sin x \): \[ \sin 46^\circ = \sin(90^\circ - 46^\circ) = \sin 44^\circ \] Using the sine addition formula: \[ \sin 44^\circ = \sin(23^\circ + 23^\circ) = 2\sin 23^\circ \cos 23^\circ = 2\sqrt{1 - t} \sqrt{t} = 2\sqrt{t(1 - t)} \] ### Step 5: Determine \( \tan(-226^\circ) \) Using the periodicity of the tangent function: \[ \tan(-226^\circ) = \tan(360^\circ - 226^\circ) = \tan(134^\circ) \] Using the identity \( \tan(180^\circ - x) = -\tan x \): \[ \tan(134^\circ) = -\tan(46^\circ) \] Using the identity \( \tan x = \frac{\sin x}{\cos x} \): \[ \tan(46^\circ) = \frac{\sin 46^\circ}{\cos 46^\circ} = \frac{2\sqrt{t(1 - t)}}{2t - 1} \] Thus, \[ \tan(-226^\circ) = -\frac{2\sqrt{t(1 - t)}}{2t - 1} \] ### Step 6: Determine \( \sin 37^\circ \) Using the identity \( \sin(90^\circ - x) = \cos x \): \[ \sin 37^\circ = \cos(90^\circ - 37^\circ) = \cos 53^\circ \] Using the identity \( \cos(90^\circ - x) = \sin x \): \[ \sin 37^\circ = \sin(90^\circ - 53^\circ) = \sin 53^\circ \] Using the sine addition formula: \[ \sin 53^\circ = \sin(23^\circ + 30^\circ) = \sin 23^\circ \cos 30^\circ + \cos 23^\circ \sin 30^\circ \] Substituting known values: \[ \cos 30^\circ = \frac{\sqrt{3}}{2}, \quad \sin 30^\circ = \frac{1}{2} \] Thus, \[ \sin 53^\circ = \sqrt{1 - t} \cdot \frac{\sqrt{3}}{2} + \sqrt{t} \cdot \frac{1}{2} \] ### Summary of Results 1. \( \sin^2 337^\circ = 1 - t \) 2. \( \sin 23^\circ = \sqrt{1 - t} \) 3. \( \cos 46^\circ = 2t - 1 \) 4. \( \sin 46^\circ = 2\sqrt{t(1 - t)} \) 5. \( \tan(-226^\circ) = -\frac{2\sqrt{t(1 - t)}}{2t - 1} \) 6. \( \sin 37^\circ = \sqrt{1 - t} \cdot \frac{\sqrt{3}}{2} + \sqrt{t} \cdot \frac{1}{2} \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To express each of the given trigonometric functions in terms of \( t = \cos^2 23^\circ \), let's compute them step by step. 1. **For \( \sin ^{2} 337^{\circ} \)**: \[ \sin^2 337^\circ = \sin^2 (-23^\circ) = \sin^2 23^\circ = 1 - \cos^2 23^\circ = 1 - t. \] 2. **For \( \sin 23^{\circ} \)**: \[ \sin 23^\circ = \sqrt{1 - \cos^2 23^\circ} = \sqrt{1 - t}. \] 3. **For \( \cos 46^{\circ} \)**: \[ \cos 46^\circ = \cos(2 \times 23^\circ) = 2 \cos^2 23^\circ - 1 = 2t - 1. \] 4. **For \( \sin 46^{\circ} \)**: \[ \sin 46^\circ = \sin(2 \times 23^\circ) = 2 \sin 23^\circ \cos 23^\circ = 2 \sqrt{1 - t} \cdot \sqrt{t} = 2 \sqrt{t(1 - t)}. \] 5. **For \( \tan \left(-226^{\circ}\right) \)**: \[ \tan(-226^\circ) = \tan(134^\circ) = -\tan(46^\circ) = -\frac{\sin 46^\circ}{\cos 46^\circ} = -\frac{2 \sqrt{t(1 - t)}}{2t - 1}. \] 6. **For \( \sin 37^{\circ} \)**: \[ \sin 37^\circ = \sin(90^\circ - 53^\circ) = \cos 53^\circ = \sin 23^\circ = \sqrt{1 - t}. \] Thus, summarizing in terms of \( t \): 1. \( \sin^2 337^\circ = 1 - t \) 2. \( \sin 23^\circ = \sqrt{1 - t} \) 3. \( \cos 46^\circ = 2t - 1 \) 4. \( \sin 46^{\circ} = 2\sqrt{t(1-t)} \) 5. \( \tan(-226^\circ) = -\frac{2\sqrt{t(1-t)}}{2t - 1} \) 6. \( \sin 37^\circ = \sqrt{1 - t} \)

Related Questions

8. Simplify without using a calculator. (8.1) \( \frac{\sin \left(180^{\circ}-x\right) \cdot \tan \left(360^{\circ}-x\right)}{\cos \left(80^{\circ}-x\right)} \times \frac{\cos \left(-180^{\circ}-x\right)}{\cos \left(360^{\circ}+x\right) \sin \left(360^{\circ}-x\right)} \) \( 8.2 \frac{\cos 135^{\circ} \sin 160^{\circ}}{\sin 225^{\circ} \cos 70^{\circ}} \) (8.3) \( \frac{\sin (-\theta)+\cos 120^{\circ}+\tan \left(-180^{\circ}-\theta\right)}{\sin ^{2} 225^{\circ}-\tan (-\theta)-\cos \left(90^{\circ}+\theta\right)} \) B.4 \( 4^{x} \frac{\sin 247^{\circ} \cdot \tan 23^{\circ} \cdot \cos 113^{\circ}}{\sin \left(-157^{\circ}\right)} \) (8.5) \( \frac{3 \cos 150^{\circ} \cdot \sin 270^{\circ}}{\tan \left(-45^{\circ}\right) \cdot \cos 600^{\circ}} \) 8.6) \( \frac{\tan \left(180^{\circ}-x\right) \cdot \sin \left(90^{\circ}+x\right)}{\sin (-x)}-\sin y \cdot \cos \left(90^{\circ}-y\right) \) \( 8.7 \frac{\tan 30^{\circ} \cdot \sin 60^{\circ} \cdot \cos 25^{\circ}}{\cos 135^{\circ} \cdot \sin \left(-45^{\circ}\right) \cdot \sin 65^{\circ}} \) 6.8) \( \frac{\tan \left(180^{\circ}-x\right) \cdot \sin \left(90^{\circ}-x\right)}{\cos \left(90^{\circ}+x\right)}-\frac{\cos \left(180^{\circ}-x\right)}{\sin \left(90^{\circ}+x\right)} \) \( 8.9 \frac{\sin 189^{\circ}}{\tan 549^{\circ}}-\frac{\cos ^{2}\left(-9^{\circ}\right)}{\sin 99^{\circ}} \) Solving trigonometric equations (no calculators) (1.) If \( \sin \mathrm{A}=\frac{-3}{5} \) and \( 0^{\circ}<\mathrm{A}<270^{\circ} \) determine the value of: \( 1.1 \cos A \) \( 1.2 \tan A \). (2.) If \( -5 \tan \theta-3=0 \) and \( \sin \theta<0 \), determine: \( 2.1 \sin ^{2} \theta^{\circ} \) \( 2.25 \cos \theta \) \( 2.3 \quad 1-\cos ^{2} \theta \) 3. If \( 13 \cos \theta+12=0 \) and \( 180^{\circ}<\theta<360^{\circ} \), evaluate: \( 3.2 \tan \theta \) \( 3.1 \sin \theta \cos \theta \) \( 3.3 \sin ^{2} \theta+\cos ^{2} \theta \). (4.) If \( 3 \tan \theta-2=0 \) and \( \theta \in\left[90^{\circ} ; 360^{\circ}\right] \), determine, the value of \( \sqrt{13}(\sin \theta-\cos \theta \) (5.) If \( \cos 52^{\circ}=k \) as illustrated in the diagram, determine each of the following i
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy